Evaluating the Effectiveness of Multidimensional Social-Emotional Learning (SEL) Programs in Reducing School Bullying: A Global Systematic Literature Review of Primary and Secondary Education Interventions (2014-2024) - Aulia Zakiyah Almardiyah; Rika Dwi Agustiningsih; Rovi Husnaini (IJIP : Indonesian Journal of Islamic Psychology, 2025)
ullying remains a pervasive global issue with adverse effects on students’ psychosocial development, school engagement, and mental health. Social-Emotional Learning (SEL) is increasingly recognized as a holistic, preventive framework that fosters competencies such as self-awareness, self-management, social awareness, relationship skills, and responsible decision-making, which are directly linked to bullying prevention. This study employed a Systematic Literature Review (SLR) guided by PRISMA 2020 standards and the STAMP framework to ensure methodological rigor and transparency. Six electronic databases were systematically searched, yielding 2,527 records. After screening and quality appraisal, 21 peer-reviewed studies published between 2014 and 2024 were included for thematic synthesis. Findings show that SEL interventions effectively reduce bullying and enhance protective psychosocial factors. Long-term, curriculum-embedded, and multi-component programs demonstrated the most consistent outcomes, while short-term interventions yielded mixed effects. Selective interventions targeting high-risk students produced stronger reductions in victimization, whereas universal programs enhanced resilience and improved classroom climate. Participatory and digital delivery formats increased student engagement but showed variable behavioral impacts. Cultural adaptation emerged as a critical moderator, with contextually tailored programs demonstrating greater effectiveness. SEL represents a promising whole-school strategy for bullying prevention, but its success depends on sustained implementation, program comprehensiveness, and cultural alignment. Practical implications include embedding SEL into curricula and supplementing universal programs with targeted interventions for vulnerable groups. Research limitations include small samples, reliance on self-reports, and limited longitudinal designs. Future research should employ rigorous randomized controlled trials, standardized outcome measures, and cross-cultural approaches to strengthen evidence-based practice and inform global education policy.